Factors affecting service learning implementation: a comparison of novice and veteran teachers. Issue 6 (18th August 2018) - Losser, Janet L.; Caldarella, Paul; Black, Sharon J.; Pate, P. Elizabeth
ABSTRACT: This qualitative study investigated factors that facilitate and hinder implementation of service learning for novice and veteran teachers. We conducted case studies of three novice teachers and three veteran teachers, using a cross-case analysis within and across groups. Confirming prior research, facilitating factors included teachers' knowledge of service learning and availability of time for planning and enacting it. Some novel factors contributing to the literature included student characteristics and common core pressures. Findings indicated differing needs of novice and veteran teachers for learning about and implementing service learning. Study implications and limitations are addressed.